2019
DOI: 10.3390/ijms20051253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eleutherococcus Extract Mixture on Endochondral Bone Formation in Rats

Abstract: Eleutherococcus extract mixture (EEM) is an herbal mixture of dried stem of Eleutherococcus sessiliflorus and germinated barley, which has been highly effective, in previous screening and among the traditional medicines to tonify innate qi and acquired qi, respectively. In this study, we investigate the effects of EEM on endochondral bone formation. Female adolescent rats were given EEM, growth hormone or vehicle for 10 days. Tetracycline was intraperitoneally injected to light the fluorescent band 72 h before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Indeed, the administration of EEM markedly increased the intensity of IGF-1 expressions in the proliferative and hypertrophic zones of growth plate. Also, EEM was significantly increased in liver IGF-1 and IGFBP-3 mRNA expressions [39].…”
Section: Eleutherococcus Sessiliflorus and Barley Mixture (Eem)mentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, the administration of EEM markedly increased the intensity of IGF-1 expressions in the proliferative and hypertrophic zones of growth plate. Also, EEM was significantly increased in liver IGF-1 and IGFBP-3 mRNA expressions [39].…”
Section: Eleutherococcus Sessiliflorus and Barley Mixture (Eem)mentioning
confidence: 91%
“…Barley has been demonstrated to effectively remove superoxide anion radicals [38]. In vivo experiments have confirmed that EEM, a standardized mixture of these two components, E. sessiliflorus and barley, promotes bone length growth in rats [39]. Briefly, the length of the proximal tibial growth plate was increased by the oral administration of EEM 50 mg/kg and 200 mg/kg for 7 days…”
Section: Eleutherococcus Sessiliflorus and Barley Mixture (Eem)mentioning
confidence: 96%
“…In previous studies involving adolescent rats, 50, 100, 200, and 300 mg/kg of herbal compounds and 100 and 500 mg/kg of herbs significantly increased longitudinal bone growth, while 30 mg/kg of herbs did not significantly enhance bone growth compared with the control group [4][5][6][7][32][33][34]. Amounts of 100 and 200 mg/kg of A. macrostemon had an antidepressant effect, while 400 mg/kg of A. macrostemon showed no effect in mice [35].…”
Section: Weight and Feed Intake Check A Macrostemon Administrationmentioning
confidence: 99%
“…Studies have shown that IGFBP3 can be used as a therapeutic target for lung adenocarcinoma metastasis to the brain [ 17 ]. Increasing expression of IGFBP3 could promote the formation of endothelial bone in rats fed with eleutherococcus extract mixture (EEM) [ 18 ]. The enhanced transcription of IGFBP3 accumulates the abundance of IGF1 , which affects the growth and metabolism of mice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%